Baseline caspase activity predicts progression free survival of temsirolimus-treated head neck cancer patients. Issue 12 (August 2015) - John, Katharina; Rösner, Imme; Keilholz, Ulrich; Gauler, Thomas; Bantel, Heike; Grünwald, Viktor
Abstract Squamous cell cancer of the head and neck (SCCHN) is a frequent aggressive malignancy with limited therapeutic options. Increasing evidence suggests that mammalian target of rapamycin (mTOR)-inhibitors might be effective in advanced SCCHN. However, non-invasive biomarkers for early prediction of treatment efficacy are not established in SCCHN. Highly proliferating tumours are characterised by enhanced cell turnover which is associated with enhanced apoptosis. During apoptosis of epithelial cells caspases cleave cytokeratin (CK)-18 can be detected in the blood. In this study we analysed sera from patients with relapsed or metastatic SCCHN patients who have been treated with temsirolimus for caspase-cleaved and total (caspase-cleaved and uncleaved) CK-18 by enzyme-linked immunosorbent assays (ELISAs). In addition, caspase-3 activity was detected by luminometric substrate assay. SCCHN patients revealed higher serum levels of those biomarkers compared to healthy controls. Importantly, patients with short progression-free survival (PFS) showed higher serum levels of caspase-3 activity compared to patients with longer PFS (⩾2 months). Caspase-3 activity is inversely correlated with PFS. A cut-off value for caspase-3 activity was determined that correctly predicted PFS <2 months with a sensitivity of 86% and a specificity of 67%. These data demonstrate that detection of serum caspase-3 activity might be a useful non-invasive biomarker for early identification of SCCHN patients not responding to treatment with novel targeted therapies such as mTOR-inhibitors.